Formation of hole-edge cracks in a combustor liner of an aero engine. (September 2015) - Chen, Y.D.; Feng, Q.; Zheng, Y.R.; Ding, X.F.
Highlights: Microstructural degradation of combustor liner after service are characterized. Service temperature of is evaluated by thermal exposure experiment. Intergranular oxidation can induce initiation of thermal fatigue cracks. The cause of hole-edge cracks formation are clarified. Abstract: A combustor liner from an aircraft engine, which is made of a wrought Ni-based superalloy GH3039, was investigated after service exposure of 1600 engine operating hours. A series of experiments, including macroscopic examination and microscopic examination, fractography observation and thermal exposure experiments, were conducted to investigate the formation mechanism of hole-edge cracks. The results show that microstructural degradation and thermal fatigue should be responsible for the formation of hole-edge cracks in complementary combustion zone (CCZ) of the combustor liner. CCZ is the highest temperature area instead of primary combustion zone (PCZ) during service, which results in significant microstructural degradation, e.g., the stripping of coating and intergranular oxidation, in the hole-edge in CCZ. The cracks initiate at the hole-edge due to coating microstructure degradations and intergranular Al2 O3 -type oxidation under the coating, and then propagate under the action of thermal fatigue, which results in final failure of the combustor liner.